Gnostic Processes in Animals - Santibáñez-H., Guy; Dominichetti C., Juan E.; Sanhueza Z., Marcelo (Revista de Psicología, 2003)
A comparison of the psycho physiological functions that underlie adaptation in nonhuman animals with the corresponding ones in Homo sapiens leads to the conclusion that they are analogous. Non human animals are not only capable of behaving, but they also exhibit subjective phenomena and are able to operate with knowledge. The above mentioned functions are based on three so called “integrative activities of the brain”. Primates possess incredible abilities: individuals from some species can operate with a language designed for deaf-mutes, and are also able to learn a computationally based language designed especially for them, called ”Yerkes”. This language allows communication between the researcher and the animals and also between two animals. Many non human primate societies are governed by strict norms, they perform play activities, they use tools and discover solutions for complex problems. Members of many animal species learn my imitation, obey orders, react to signals from their co specifics. In this paper we refer to these subjective phenomena and to the factors that integrate the set of psycho physiological processes in these non human animals. We discuss the adaptive significance of these functions and review some recent studies that reveal that certain Gnostic abilities lead to neogenesis of neurons in adult vertebrates.